(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This study aims to analyze the influence of instagram social media-based advertising on repurchase intention with customer satisfaction as a mediating variabel. The sample in this study were 120 people with a purposive sampling technique which is part of the non-probability sampling. The method used in this study is structural analysis using variance-based aquation modeling, namely partial least squares. The result of this study : instagram social media advertising significantly effect on customer saticfaction variabel. Customer saticfaction significantly influence repurchase intention variabel. Instagram social media have no effect on repurchase intention. Customer satisfaction acts as a mediating effect of instagram social media advertising on repurchase intention.